Vrednote prostora v procesu geografskega izobraževanja - Resnik Planinc, Tatjana (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2008)
Across Europe the need for finding new methodologies for the teaching of space-related topics in primary and secondary schools is perceived. Accordingly, the author suggests possibilities for the development of geography teaching; particularly with regard to subject areas concerning sustainable development, values of space, and increasing the public awareness of both. The paper discusses the options, tendencies and potential obstacles towards the implementation of those topics into geography as well as into other curricula and looks at the differences between expectation, and the actual delivery.
Keywords: geografija; geography; prostor; sustainable development; trajnostni razvoj; sonaravni razvoj; vrednote; izobraževanje; education; pouk